Políticas públicas de esporte e lazer: características nos municípios da Quarta Colônia/RS - Koltermann, Vivianne Costa (2019)
This study aims to diagnose and analyze the characteristics of Sports and Leisure Public Policies in the municipalities of the region of Quarta Colônia / RS, in which, through analysis of documents and interviews, we analyze, among public sports and leisure policies, categories of objectives and of the contents / methods found in these policies, investigating the proposals foreseen in each management and what was executed during the government, the proposals of the government plans and the executions, as well as the relation of the available financial resources for this area. The quantitative coverage of the public policies developed in the cities studied will also be analyzed.